Coated zirconium oxide particles and method for producing the same

By covering the metal compound layer of Mg, Ca, Al and rare earth elements on the surface of zirconia particles, the problem of cracks and damage easily in high temperatures is solved, and the high density and stability of the sintered body is achieved, and it is suitable for a variety of application scenarios.

CN114829304BActive Publication Date: 2025-04-15KANTO DENKA IND CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080089911.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-24
Filing Date
2020-12-23
Publication Date
2025-04-15
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

Existing zirconia particles are prone to cracks and damage at high temperatures, and volume expansion and contraction at low temperatures lead to poor quality of the sintered body.

Method used

The coated zirconia fine particles are formed by coating a compound layer of metal elements selected from Mg, Ca, Al and rare earth elements on the surface of the zirconia fine particles. The cladding layer can be produced by adding ions and alkaline substances of corresponding metal elements to the aqueous dispersion containing zirconia fine particles for neutralization.

Benefits of technology

The coated zirconia particles can suppress cracks and damage during the sintering process, improve the density and stability of the sintered body, and are suitable for various ceramic materials, dental materials, capacitors, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention is a coated zirconium oxide fine particle, which comprises zirconium oxide fine particles and a coating layer covering the surface of the fine particles, wherein the coating layer contains one or more metal elements selected from Mg, Ca, Al and rare earth elements, has an average particle size of 3 to 100 nm, and a specific surface area of ​​20 to 500 m 2 / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to coated zirconium oxide particles and methods for making the same. Background Art

[0002] Zirconium oxide (ZrO2) has many excellent characteristics such as high refractive index, high strength, high toughness, high wear resistance, high lubricity, high corrosion resistance, high oxidation resistance, insulation, low thermal conductivity, and high transparency in the visible light region. Therefore, it can be used in various applications such as catalysts for automobile exhaust gas, capacitors, crushing balls, dental materials, glass additives, heat barrier layers, solid electrolytes, and optical materials.

[0003] Zirconia is used in the manufacture of various articles by, for example, forming and sintering fine particles. However, as a single body, there is a problem that it forms a tetragonal crystal structure at high temperatures and a monoclinic crystal structure at low temperatures. Therefore, due to volume expansion and contraction caused by temperature changes, cracks are easily generated on the sintered body and it is broken. Therefore, a method is generally adopted in which stabilizers such as yttrium oxide (Y2O3), calcium oxide (CaO), magnesium oxide (MgO), and cerium oxide (CeO2) are dissolved in zirconium oxide without causing phase change. Zirconia that is partially stabilized by adding a stabilizer is also called partially stabilized zirconium oxide.

[0004] The partially stabilized zirconia can be produced by various methods such as a neutralization method, a hydrolysis method, a hydrothermal reaction method, an alkoxide method, a gas phase method, and a spray pyrolysis method, depending on the method for producing zirconia.

[0005] Japanese Patent Application Publication No. 2008-24555 discloses a method of adding a compound such as yttrium as a stabilizer to a hydrated zirconium sol, drying the sol, and calcining the sol at 1000 to 1200° C. to produce a zirconium oxide fine powder containing one or more of yttrium oxide, calcium oxide, magnesium oxide, and cerium oxide as a stabilizer.

[0006] Japanese Patent Gazette No. 2010-137998 discloses a method for producing a partially stabilized zirconia ceramic containing zirconium oxide and yttrium oxide in a specified range, wherein yttrium oxide microparticle powder or yttrium salts are uniformly dispersed in zirconium hydroxide as a starting material containing Zr to obtain a composite, zirconium oxide is obtained by heat treating the obtained composite in a temperature range of 1100 to 1400°C, the zirconium oxide is crushed to obtain a ceramic powder, and the ceramic powder is formed and sintered.

[0007] In Japanese Patent Gazette No. 2015-221727, a method for producing a specific zirconium oxide sintered body containing 0.05 to 3 mass % of aluminum oxide and a yttria concentration of 2 to 4 mol %, is disclosed, wherein the average particle size of the secondary particles is 0.1 to 0.4 μm, and the ratio of the average particle size of the secondary particles to the average particle size of the primary particles measured by an electron microscope is 1 to 8, and a zirconium oxide powder containing 0.05 to 3 mass % of an aluminum compound converted as aluminum oxide and a yttria concentration of 2 to 4 mol % is formed, pre-sintered at 1100 to 1200° C., and the obtained pre-sintered body is subjected to hot gas hydrostatic pressure treatment under the conditions of a pressure of 50 to 500 MPa and a temperature of 1150 to 1250° C.

[0008] Japanese Patent Gazette No. 2009-227507 discloses a method for producing zirconium oxide composite particles, which is characterized in that an alkali metal carbonate solution is added to an acidic dispersion of zirconium oxide containing rare earth element ions and / or alkaline earth metal ions to generate a neutralized precipitate, the neutralized precipitate is then dried, the dried neutralized precipitate is heat-treated at a temperature of not less than 400° C. and not more than 600° C., and then washed to remove the alkali metal carbonate component.

[0009] Japanese Patent Gazette No. 5-170442 discloses a method for producing a crystalline zirconium oxide sol in which a rare earth element oxide, calcium oxide or magnesium oxide is solid-solved, wherein a solution of a zirconium salt and a solution of a salt selected from a rare earth element, calcium or magnesium are mixed in advance, the mixed solution is added to an alkaline solution or a slurry of an alkaline substance, the resulting slurry is heated at a temperature of 80 to 200°C, and after adding an acid, the slurry is separated and washed.

[0010] Japanese Patent Application Publication No. 2017-154927 discloses zirconium oxide nanoparticles coated with carboxylic acid, wherein the zirconium oxide nanoparticles contain yttrium and at least one transition metal other than rare earth elements. Summary of the invention

[0011] Japanese Patent Publication No. 2008-24555, Japanese Patent Publication No. 2010-137998, Japanese Patent Publication No. 2015-221727 and Japanese Patent Publication No. 2009-227507 utilize a neutralization method and / or a hydrolysis method, but require sintering at a high temperature for solid solution, and the particle shape is non-uniform due to particle growth, and particles with poor dispersibility are easily formed.

[0012] On the other hand, Japanese Patent Publication No. 5-170442 and Japanese Patent Publication No. 2017-154927 are methods using a hydrothermal reaction method, which do not require a calcination process, so that a fine particle size can be obtained, which is considered to be advantageous for obtaining zirconium oxide particles of the order of tens of nanometers. However, yttrium salts that are fully utilized as stabilizers generally have lower solubility than zirconium salts. Therefore, in methods using a hydrothermal reaction method, it is difficult to uniformly mix zirconium and yttrium at the atomic level in industrial-scale production, and there is a tendency for yttrium oxide to be uneven. In addition, since the reaction takes a long time, there is a problem in terms of productivity.

[0013] In view of the above circumstances, the present invention provides stable zirconium oxide fine particles and a simple method for producing the same.

[0014] The present invention relates to coated zirconium oxide fine particles comprising zirconium oxide fine particles and a coating layer coating the surface of the fine particles, wherein:

[0015] The coating layer contains one or more metal elements selected from Mg, Ca, Al and rare earth elements.

[0016] The average particle size is 3 to 100 nm.

[0017] Specific surface area is 20~500m 2 / g.

[0018] In addition, the present invention relates to a method for producing coated zirconium oxide particles, wherein ions of one or more metal elements selected from Mg, Ca, Al and rare earth elements and an additive that reacts with the aforementioned ions to form a water-insoluble compound are reacted in an aqueous dispersion containing zirconium oxide particles, so that the compound containing the aforementioned metal element is precipitated on the surface of the zirconium oxide particles to obtain coated zirconium oxide particles.

[0019] According to the present invention, stable coated zirconium oxide fine particles and a simple method for producing the same can be provided.

[0020] The coated zirconium oxide particles of the present invention have advantages over conventional zirconium oxide particles in that cracks and damage of the sintered body can be suppressed during the firing process and that the density can be increased, and therefore are suitable for use in various ceramic materials, dental materials, capacitors, coating materials, etc. In addition, the coated zirconium oxide particles of the present invention can be produced by a simple method, so that the production cost can be reduced, and are useful in industrial-scale production.

[0021] Brief description of the attached figure

[0022] Figure 1 This is a transmission electron microscope (TEM) image of the coated zirconium oxide fine particles obtained in Example 2.

[0023] Figure 2 The images are scanning electron microscope / energy dispersive X-ray spectroscopy (SEM-EDX) images showing the element distribution of zirconium and yttrium in the coated zirconium oxide fine particles obtained in Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0024] [Coated zirconium oxide particles]

[0025] The present invention relates to coated zirconium oxide particles, which contain zirconium oxide particles and a coating layer covering the surface of the particles, wherein the coating layer contains one or more metal elements selected from Mg, Ca, Al and rare earth elements, and has an average particle size of 3 to 100 nm and a specific surface area of ​​20 to 500 m 2 / g.

[0026] The specific surface area of ​​the zirconium oxide particles is preferably 20 to 500 m 2 / g, more preferably 40 to 200 m 2 / g, more preferably 70 to 150 m 2 / g. The specific surface area of ​​zirconium oxide particles is 20m 2 When the surface area of ​​the zirconium oxide particles is 500 m / s or more, the particle size of the obtained coated zirconium oxide particles can be appropriately suppressed, and a high-density sintered body can be easily obtained. In addition, there is a tendency to easily show the stabilization effect brought by the metal element of the coating layer. 2 When the particle size is not more than 100 μm, the particle size is appropriately large and the cohesive force is not excessively large, so that monodispersity is easily achieved during surface coating and the filling property during molding when the coated zirconium oxide fine particles are used is also improved.

[0027] Here, the specific surface area of ​​the zirconium oxide fine particles can be measured by the BET method based on nitrogen adsorption and desorption of a sample degassed at 150° C. using a BET specific surface area measuring device, for example, a fully automatic BET specific surface area measuring device (Macsorb HM Model-1210) manufactured by Mounttech.

[0028] The average particle size of the zirconium oxide particles is preferably 3 to 100 nm, more preferably 5 to 50 nm, and further preferably 7 to 20 nm. In the present invention, the average particle size of the zirconium oxide particles can be obtained by measuring the particle sizes of 200 or more arbitrary particles from a TEM image at a magnification of 200,000 times based on observation using a transmission electron microscope, and obtaining the average particle size from the average particle size.

[0029] The coated zirconium oxide fine particles of the present invention have a coating layer containing one or more metal elements selected from Mg, Ca, Al and rare earth elements on the surface of the zirconium oxide fine particles.

[0030] One or more metals selected from Mg, Ca, Al and rare earth elements contribute to stabilization of the zirconium oxide fine particles.

[0031] The rare earth element is preferably Y (yttrium).

[0032] The coating layer may contain a compound containing one or more metal elements selected from Mg, Ca, Al and rare earth elements (hereinafter also referred to as a coating compound).

[0033] The coating layer may be a layer containing one or more compounds selected from hydroxides of one or more metal elements selected from Mg, Ca, Al and rare earth elements, carbonates of the foregoing metal elements and oxides of the foregoing metal elements.

[0034] The coating layer is preferably a layer containing one or more compounds selected from hydroxides of one or more metal elements selected from Mg, Ca, Al and Y, carbonates of the foregoing metal elements and oxides of the foregoing metal elements.

[0035] The coating layer preferably contains Y, more preferably contains an yttrium compound such as yttrium hydroxide, and further preferably contains a hydroxide.

[0036] By adding the aforementioned metal elements, for zirconium oxide particles, the phase transition from tetragonal to monoclinic can be suppressed, and the strength, durability and dimensional accuracy are improved. From this point of view, the amount of the aforementioned metal elements can be adjusted. For example, in the present invention, the amount of the coating compound in the coating layer is preferably 3 to 45 mol%, more preferably 5 to 40 mol%, further preferably 6 to 36 mol%, and further preferably 12 to 28 mol% relative to the zirconium oxide of the zirconium oxide particles. When the amount of the coating compound in the coating layer is above the aforementioned lower limit, the tetragonal rate in the crystal structure after high-temperature sintering becomes appropriately larger, the crack and damage suppression effect of the sintered body is large, and the production of the formed body also becomes easy. In addition, when the amount of the aforementioned metal element in the coating layer is below the aforementioned upper limit, the bending strength and fracture toughness can be maintained, and it is difficult to generate an impurity phase derived from the stabilizer after high-temperature sintering, and the strength, insulation and other characteristics of the sintered body also become good. It should be noted that the amount of the coating compound in the coating layer can be obtained by measuring using XRF analysis methods and the like. Alternatively, the coating compound estimated from the type and amount of the compound used for coating, the type of neutralizer used for neutralizing the compound, etc. can be determined and obtained by calculation.

[0037] The average particle size of the coated zirconium oxide particles of the present invention is 3 to 100 nm, preferably 5 to 50 nm, and more preferably 7 to 20 nm. The average particle size of the coated zirconium oxide particles can be obtained as follows: based on observation using a transmission electron microscope, the particle size of more than 200 arbitrary particles is measured according to a TEM image with a magnification of 200,000 times, and the average value is obtained. By controlling the particle size, the transparency of the composition containing the coated zirconium oxide particles can be improved. In addition, the low temperature sintering property is excellent.

[0038] The specific surface area of ​​the coated zirconium oxide particles of the present invention is 20 to 500 m 2 / g, preferably 40 to 200 m 2 / g, more preferably 70 to 150 m 2 / g. The specific surface area of ​​the coated zirconium oxide particles is 20m 2 When the particle size is above 500 / g, the particles are formed into particles with appropriately suppressed particle size, so it is easy to obtain a high-density sintered body. In addition, there is a tendency to easily show the stabilization effect brought by the metal element of the coating layer. In addition, the specific surface area of ​​the coated zirconium oxide particles is 500m 2 When the particle size is less than 1.5 μm / g, the particle size becomes appropriately large and the cohesive force does not become excessively large, so the filling property during molding becomes good.

[0039] The coated zirconium oxide fine particles of the present invention can be suitably used in various ceramic materials, dental materials, capacitors, coating materials, and the like.

[0040] [Method for producing coated zirconium oxide fine particles]

[0041] The present invention relates to a method for producing coated zirconium oxide particles, wherein ions of one or more metal elements selected from Mg, Ca, Al and rare earth elements and an additive that reacts with the ions to form a water-insoluble compound are reacted in an aqueous dispersion containing zirconium oxide particles, and a compound (coating compound) containing the metal elements is precipitated on the surface of the zirconium oxide particles to obtain coated zirconium oxide particles. In the production method of the present invention, the matters described in the present invention for coated zirconium oxide particles can be appropriately applied. The coated zirconium oxide particles of the present invention can be obtained by the production method of the present invention. For example, the preferred embodiments of the zirconium oxide particles and the metal elements as raw materials are the same as those described in the present invention for coated zirconium oxide particles.

[0042] The above-mentioned additives include, for example, alkaline substances. As alkaline substances, hydroxides such as NaOH and KOH, carbonates such as Na2CO3, K2CO3, ammonium carbonate, NaHCO3, KHCO3, ammonia, etc. can be mentioned. These alkaline substances can be used in the form of aqueous solutions, powders, solids, and crystals. From the perspective of easy operation, aqueous solutions are preferred. In addition, aqueous ammonia solutions can also be used as alkaline substances. When using alkaline substances in aqueous solutions, the concentration is preferably 5 to 50% by mass, more preferably 10 to 30% by mass.

[0043] In the present invention, the ions of the metal element may be introduced into the aqueous dispersion of zirconium oxide fine particles by mixing an aqueous solution containing a compound of the metal element into the aqueous dispersion.

[0044] In the present invention, the aqueous dispersion, the aqueous solution of the compound containing the metal element, and the additive may be mixed to react the ions with the additive. In this case, the aqueous solution of the compound containing the metal element and the additive are used so that the amount of the coating compound formed by the compound and the additive is preferably 3 to 45 mol%, more preferably 5 to 40 mol%, further preferably 6 to 36 mol%, and further preferably 12 to 28 mol% relative to the zirconium oxide of the zirconium oxide fine particles in terms of the maximum theoretical value.

[0045] In the present invention, the additives may be removed from the coated zirconium oxide fine particles after the coated zirconium oxide fine particles are obtained. For example, the coated zirconium oxide fine particles may be washed with water after the coated zirconium oxide fine particles are obtained.

[0046] In the present invention, the obtained coated zirconium oxide particles may be dried, and the temperature at this time may be set to a temperature at which the coated zirconium oxide fine particles are not sintered, for example, 200° C. or less.

[0047] In the present invention, an alkaline substance is added to an aqueous dispersion containing zirconium oxide fine particles and mixed uniformly, and then an aqueous solution containing the compound of the metal element is added to perform a neutralization reaction so that the metal compound is uniformly coated on the particle surface of the zirconium oxide fine particles.

[0048] In the present invention, an aqueous solution containing the compound of the metal element is added to an aqueous dispersion containing zirconium oxide fine particles, and then an alkaline substance is added to perform a neutralization reaction so that the metal compound is uniformly coated on the particle surface of the zirconium oxide fine particles.

[0049] In the present invention, an aqueous solution of a compound containing the metal element and an alkaline substance may be simultaneously added to an aqueous dispersion containing zirconium oxide fine particles to perform a neutralization reaction so that the metal compound is uniformly coated on the particle surface of the zirconium oxide fine particles.

[0050] An example of the method for producing the coated zirconium oxide fine particles of the present invention will be described.

[0051] First, zirconium oxide particles are uniformly dispersed in water. In order to uniformly disperse the zirconium oxide particles, pH adjustment is preferably performed using a dispersing machine such as an ultrasonic homogenizer, a planetary ball mill, a Henschel mixer, a colloid mill, a wet air jet mill, or a wet bead mill. Alternatively, a mechanical stirrer or the like may be used.

[0052] The aqueous dispersion of zirconium oxide particles thus obtained is mixed with a composition containing ions of one or more metal elements selected from Mg, Ca, Al and rare earth elements and water. The aforementioned composition is preferably an aqueous solution of a compound of the aforementioned metal element, such as a salt. As salts containing the aforementioned metal element, inorganic salts such as sulfates, nitrates, and chloride salts can be cited. In addition, organic compounds such as metal alkoxides can be used. Inorganic salts are preferred from the perspective of solubility and ease of acquisition. The concentration of the aqueous solution is preferably 0.001 to 10 mol / L, more preferably 0.01 to 5 mol / L.

[0053] Next, an additive that reacts with the ions to generate a water-insoluble compound is mixed with a mixture of an aqueous dispersion of zirconium oxide particles and a composition containing the metal element ions and water, preferably an aqueous solution containing a compound (eg, salt) of the metal element.

[0054] Examples of the additive include the aforementioned alkaline substances, for example, aqueous solutions of alkaline substances.

[0055] When a salt containing the above-mentioned metal element is used, the alkaline substance is added in such an amount that the degree of neutralization of the salt becomes, for example, 0.8 or more.

[0056] The temperature when adding the alkaline substance is not particularly limited, and may be, for example, 100° C. or lower.

[0057] In the present invention, for example, it can be confirmed from the state of the TEM image of the zirconium oxide fine particles that the compound containing the above-mentioned metal element covers the surface of the zirconium oxide fine particles.

[0058] The aqueous dispersion containing zirconium oxide particles uniformly coated with a metal compound is appropriately filtered, washed with water, dried, crushed, etc. to obtain coated zirconium oxide particles. In one example, the coating layer is formed of hydroxides or carbonates of Mg, Ca, Al and rare earth elements and is in an amorphous state. Alternatively, the coating layer may be formed into a crystalline state of an oxide by heat treatment.

[0059] The coated zirconium oxide particles of the present invention can be used in the form of powder, dispersion, nanocomposite, etc. The dispersion can include a dispersion using water or an organic compound as a dispersion medium. In addition, the nanocomposite can include a nanocomposite uniformly dispersed in an organic compound such as a monomer, oligomer, or resin.

[0060] As an example of the manufacturing method of the present invention, there can be cited a method for manufacturing coated zirconium oxide particles, wherein an alkaline substance is mixed in a mixture obtained by mixing an aqueous dispersion of zirconium oxide particles and an aqueous solution of a water-soluble salt of one or more metal elements selected from Mg, Ca, Al and rare earth elements so that the pH of the mixture becomes 8 to 13, preferably 12 to 13, so that a compound containing the aforementioned metal element is precipitated on the surface of the zirconium oxide particles to obtain coated zirconium oxide particles. In this case, an alkaline substance can be added so that the neutralization degree of the aforementioned water-soluble salt is 0.8 or more. In addition, in the present invention, the coated zirconium oxide particles can be washed with water until the detected amount of the alkaline substance is 0.01% by mass or less. The aforementioned water-soluble salt can be cited as a substance having a solubility of 5.0 g / 100 g of water or more in water at 20°C.

[0061] According to the present invention, there is provided a method for producing zirconium oxide fine particles, wherein ions of one or more metal elements selected from Mg, Ca, Al and rare earth elements and an additive that reacts with the ions to form a water-insoluble compound are reacted in an aqueous dispersion containing zirconium oxide fine particles.

[0062] According to the present invention, a method for producing zirconium oxide microparticles can be provided, wherein an alkaline substance is mixed in a mixture obtained by mixing an aqueous dispersion of zirconium oxide microparticles and an aqueous solution of a water-soluble salt of one or more metal elements selected from Mg, Ca, Al and rare earth elements so that the pH of the mixture is 8 to 13, preferably 12 to 13. The aforementioned aqueous solution may be an aqueous solution containing the aforementioned water-soluble salt at a concentration of 0.001 to 10 mol / L. In addition, an alkaline substance may be added so that the neutralization degree of the aforementioned water-soluble salt is 0.8 or more. In addition, in the present invention, the coated zirconium oxide particles may be washed with water until the detected amount of the alkaline substance is 0.01% by mass or less. The aforementioned water-soluble salt may include a substance having a solubility of 5.0 g / 100 g of water or more in water at 20°C.

[0063] According to the present invention, a method for producing a sintered zirconium oxide body can be provided, which comprises a step of producing coated zirconium oxide particles by the method of the present invention, and a step of sintering the produced coated zirconium oxide particles. In the method for producing a sintered zirconium oxide body, the matters described in the present invention regarding the coated zirconium oxide particles and the method for producing the coated zirconium oxide particles can be appropriately applied. The sintering of the coated zirconium oxide particles can be carried out according to a known method for sintering zirconium oxide particles, taking into account the purpose of the sintered body, etc. As an example, a method of sintering at 1300 to 1600°C for 1 to 15 hours can be cited.

[0064] According to the present invention, there is provided a method for producing a coated zirconium oxide fine particle dispersion, the method comprising dispersing the coated zirconium oxide fine particles of the present invention in a dispersion medium (hereinafter also referred to as a dispersion medium for the dispersion). In the method for producing the coated zirconium oxide fine particle dispersion, the matters described in the present invention regarding the coated zirconium oxide fine particles and the method for producing the coated zirconium oxide fine particles can be appropriately applied.

[0065] In addition, according to the present invention, there is provided a method for producing a nanocomposite, wherein the method comprises dispersing the coated zirconium oxide particles of the present invention in a dispersion medium (hereinafter also referred to as a dispersion medium for a nanocomposite). In the method for producing the nanocomposite, the matters described in the present invention regarding the coated zirconium oxide particles and the method for producing the coated zirconium oxide particles can be appropriately applied.

[0066] In the method for producing a coated zirconium oxide fine particle dispersion and a method for producing a nanocomposite of the present invention, the coated zirconium oxide fine particles of the present invention may be treated with a surface treatment agent. Examples of the surface treatment agent include the following, but are not limited thereto.

[0067] For example, a (meth)acryloyloxy-based silane coupling agent, a vinyl-based silane coupling agent, an epoxy-based silane coupling agent, an amino-based silane coupling agent, a urea-based silane coupling agent, or the like can be used.

[0068] Examples of the (meth)acryloxy-based silane coupling agent include 3-(meth)acryloxypropyltrimethylsilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, and 3-(meth)acryloxypropyltriethoxysilane. Examples of the acryloxy-based silane coupling agent include 3-acryloxypropyltrimethoxysilane.

[0069] Examples of the vinyl silane coupling agent include allyltrichlorosilane, allyltriethoxysilane, allyltrimethoxysilane, diethoxymethylvinylsilane, trichlorovinylsilane, vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltris(2-methoxyethoxy)silane.

[0070] Examples of epoxy-based silane coupling agents include diethoxy(glycidoxypropyl)methylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane. Examples of styrene-based silane coupling agents include p-styryltrimethoxysilane.

[0071] Examples of the amino-based silane coupling agent include N-2 (aminoethyl) 3-aminopropylmethyldimethoxysilane, N-2 (aminoethyl) 3-aminopropyltrimethoxysilane, N-2 (aminoethyl) 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane.

[0072] As the ureido-based silane coupling agent, 3-ureidopropyltriethoxysilane can be mentioned.

[0073] As other surface treatment agents, the following substances can be cited. As a chloropropyl-based silane coupling agent, 3-chloropropyltrimethoxysilane can be cited. As a mercapto-based silane coupling agent, 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane can be cited. As a sulfide-based silane coupling agent, bis(triethoxysilylpropyl)tetrasulfide can be cited. As an isocyanate-based silane coupling agent, 3-isocyanatepropyltriethoxysilane can be cited. As an aluminum-based coupling agent, acetylalkoxy aluminum diisopropoxide can be cited.

[0074] The dispersion medium for the dispersion used in the present invention is not particularly limited as long as it can disperse the coated zirconium oxide fine particles. For example, water or an organic compound can be used as the dispersion medium for the dispersion.

[0075] When water is used as the dispersion medium for the dispersion liquid, the pH is preferably 2 to 5, or 9 to 13, from the viewpoint of the dispersibility of the coated zirconium oxide fine particles.

[0076] The organic compound used as the dispersion medium for the dispersion liquid can be selected from compounds known as organic solvents. Specifically, preferably, for example, ethanol, isopropanol, butanol, cyclohexanol, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, ethyl acetate, propyl acetate, butyl acetate, methyl cellosolve, cellosolve, butyl cellosolve, cellosolve acetate, tetrahydrofuran, 1,4-dioxane, n-hexane, cyclopentane, toluene, xylene, N, N-dimethylformamide, N, N-dimethylacetamide, dichloromethane, trichloroethane, trichloroethylene, hydrofluoroether, etc. can be mentioned.

[0077] The dispersion medium for the nanocomposite is not particularly limited as long as it is an organic compound, such as a monomer, an oligomer, a resin (polymer), etc., which can disperse the coated zirconium oxide particles. As the monomer, oligomer, resin, etc., for example, acrylates containing aromatic rings, acrylates containing alicyclic skeletons, monofunctional (meth) alkyl acrylates, multifunctional (meth) alkyl acrylates, and polymers thereof can be used.

[0078] As the aromatic ring-containing acrylate, from the viewpoint of high refractive index, there can be mentioned phenoxyethyl acrylate, phenoxy 2-methylethyl acrylate, phenoxyethoxyethyl acrylate, 3-phenoxy-2-hydroxypropyl acrylate, 2-phenylphenoxyethyl acrylate, benzyl acrylate, phenyl acrylate, phenylbenzyl acrylate, p-cumylphenoxyethyl acrylate, and the like.

[0079] In addition, examples of acrylates containing an alicyclic skeleton include 2-acryloyloxyethyl hexahydrophthalate, cyclohexyl acrylate, dicyclopentyl acrylate, tetrahydrofurfuryl acrylate, dicyclopentyl methacrylate, and isobornyl methacrylate, from the viewpoint of having a high Abbe number and being preferred as an optical material.

[0080] In addition, monofunctional alkyl (meth)acrylates include methyl (meth)acrylate, octyl (meth)acrylate, isostearyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene oxide-modified alkyl (meth)acrylate, propylene oxide-modified alkyl (meth)acrylate, hydroxyethyl (meth)acrylate, and hydroxypropyl (meth)acrylate from the viewpoint of low viscosity.

[0081] In addition, from the viewpoint of increasing the height of the cured product, examples of the polyfunctional alkyl (meth)acrylate include (i) bifunctional (meth)acrylates such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate; (ii) tri- and tetrafunctional (meth)acrylates such as glycerol tri(meth)acrylate, trihydroxypropane tri(meth)acrylate, phosphoric acid tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and (iii) ethylene oxide and / or propylene oxide-modified products of the compounds selected from the above (i) and (ii).

[0082] In the method for producing the coated zirconium oxide particle dispersion and the method for producing the nanocomposite of the present invention, a dispersant can be used as needed. The dispersant is not particularly limited as long as it is a compound containing a group having affinity with the coated zirconium oxide particles, and preferred dispersants include anionic dispersants having acid groups such as carboxylic acid, sulfuric acid, sulfonic acid or phosphoric acid, or their salts. Among them, a phosphate ester dispersant is preferred. There is no particular limitation on the amount of the dispersant used, but it is preferably 0.1 to 30% by mass relative to the coated zirconium oxide particles. Example

[0083] Hereinafter, the coated zirconium oxide fine particles and the production method thereof of the present invention will be described with reference to Examples, but the present invention is not limited to these Examples.

[0084] It should be noted that various instrumental analyses were performed by the following methods.

[0085] (1) X-ray diffraction (XRD)

[0086] The measurement was performed using an X-ray diffraction device (D8 ADVANCE / V) manufactured by Bruker AXS, and qualitative analysis or quantitative analysis using Rietveld analysis was performed. (tetragonal crystal, monoclinic crystal, etc.)

[0087] (2) Determination of the amount of metal compound coated in coated zirconium oxide particles (XRF analysis)

[0088] The amount of each element in the coated inorganic fine particles was quantified using a fluorescent X-ray analyzer (S8 TIGER) manufactured by Bruker AXS.

[0089] (3) Determination of specific surface area (SSA)

[0090] The specific surface area was measured by the BET method based on nitrogen adsorption and desorption using a fully automatic BET specific surface area measuring device (Macsorb HM Model-1210) manufactured by MOUNTECH using coated zirconium oxide fine particles degassed at 150°C.

[0091] (4) Determination of average particle size, particle shape and uniformity evaluation

[0092] The average particle size was determined by using a transmission electron microscope (H-7600) manufactured by Hitachi High-Technologies to obtain an image of the particles at a magnification of 30,000 to 200,000 times, measuring the major axis of 200 or more particles and averaging the major axis. The particle shape was evaluated by observation of the TEM image, and the uniformity was evaluated by the measured value of the average particle size.

[0093] (5) Evaluation of surface coating uniformity

[0094] Using a field emission scanning electron microscope (SU8220) and an energy dispersive X-ray analyzer (EX-370X-MAX50) manufactured by Hitachi High-Technologies, images of the particles were acquired at a magnification of 3000 times, and element distribution was observed and evaluated by EDX mapping.

[0095] [Preparation of coated zirconium oxide particles]

[0096] <Example 1>

[0097] Pure water was added to 27.7 g (225 mmol) of zirconium oxide microparticle powder (manufactured by Kanto Denka Kogyo Co., Ltd.) with an average particle size of 10 nm to make the powder concentration 20% by mass, and stirred with a mechanical stirrer for 1 hour to prepare a zirconium oxide water slurry. 1 mol / L yttrium nitrate aqueous solution was added dropwise to the slurry in a manner of 13.5 mmol converted to yttrium nitrate, and stirred for 1 hour. Next, 25% by mass sodium hydroxide aqueous solution was added dropwise to make the neutralization degree 0.8 or more and the pH 12 to 13, and stirred for about 1 hour. The obtained slurry was filtered, washed with water until Na could not be detected by XRF measurement, and then dried at 150°C until the moisture content became less than 1%. The obtained solid was crushed in a mortar and sieved (75 μm mesh).

[0098] <Examples 2 to 13, Comparative Example 1>

[0099] According to Example 1, various coated zirconium oxides were prepared according to the formulations shown in Table 1. It should be noted that in Example 6, commercially available zirconium oxide particles mainly in monoclinic form were used as a raw material. In addition, in Example 7, sodium carbonate was used for neutralization. In addition, in Example 8, calcium chloride was used instead of yttrium nitrate. In addition, in some of the examples, a second compound was used.

[0100] The TEM image of the coated zirconium oxide particles of Example 2 is shown in Figure 1 In addition, the SEM-EDX mapping photograph of the coated zirconium oxide particles of Example 2 is shown in Figure 2 The TEM photograph shows that the particles obtained in Example 2 are spherical, and the measured value of the average particle size shows that the particles have good uniformity.

[0101] <Comparative Example 2>

[0102] Pure water was added to 27.7 g (225 mmol) of a powder of zirconium oxide fine particles with an average particle size of 5 to 10 nm (produced by Kanto Denka Kogyo Co., Ltd.) to make it 20% by mass, and stirred for 1 hour using a mechanical stirrer. 3.1 g of yttrium oxide (Y2O3) was added to the obtained slurry containing zirconium oxide fine particles, and stirred for 1 hour. The obtained slurry was filtered, washed with water, and then heated and dried at 150°C until the moisture content was less than 1%. The obtained solid was crushed in a mortar and passed through a sieve with a mesh size of 74 μm. The SEM-EDX mapping photograph of the coated zirconium oxide of Comparative Example 2 is shown in Figure 2 .

[0103] [Sintering and crystal structure changes of coated zirconium oxide particles]

[0104] The crystal structures of the coated zirconium oxide fine particles obtained in Examples 1 to 13 and Comparative Examples 1 and 2 after sintering at 1000° C. were evaluated by the following method.

[0105] The coated zirconium oxide fine particles were heated from 20°C to 1000°C in an air atmosphere over 4 hours and sintered at 1000°C for 3 hours. The crystal structure of the obtained powder was evaluated by X-ray diffraction (XRD) measurement. It should be noted that the physical properties such as the crystal structure of the coated zirconium oxide fine particles greatly change depending on the sintering conditions (temperature, time).

[0106]

Table 1

[0107]

[0108] ※1 mol% is mol% relative to zirconium oxide, indicating the amount of the coating compound based on the type and amount of raw materials, the type of neutralizer, etc.

[0109] ※2 A very small amount of Hf is included, and the amount including that amount is expressed as Zr amount in mass %.

[0110] As shown in Comparative Example 1, the tetragonal crystal ratio of the zirconium oxide fine particles not coated with the metal compound after sintering at 1000° C. was 0%, that is, the monoclinic crystal ratio was 100%. In contrast, Examples 1 to 13 showed values ​​of tetragonal crystal ratios of 20% or more.

[0111] As shown in Examples 1 to 3, it is known that by increasing the content of yttrium hydroxide as a coating compound, the tetragonal rate after sintering is increased. In particular, under the sintering conditions, as shown in Examples 2 and 3, when the yttrium hydroxide conversion contains more than 12 mol%, the tetragonal rate after sintering becomes 95% and 93%, respectively, and Y enters the zirconia lattice, presumably acting effectively as a tetragonal stabilizing element.

[0112] As shown in Comparative Example 2, the tetragonal crystal ratio was 64% when the yttrium oxide was directly coated without Y ions, which was about 30% lower than that of Example 2 in which the surface was coated with Y ion aqueous solution. Figure 2 As shown in the SEM-EDX mapping photograph of , the coating of Y becomes uneven, and it is easy to infer that the physical properties are unstable. In addition, since an impurity phase derived from the stabilizer is generated, there is a concern that it will affect the reduction of properties such as strength when formed into a sintered body.

[0113] As shown in Examples 4 to 10, the metal compound that can be used as a stabilizer is not only Y but also hydroxides and carbonates (including carbonate hydrates) of Mg, Ca, and Al. In addition, these metal compounds may be combined.

[0114] As shown in Example 6, even when raw material fine particles mainly composed of monoclinic crystals (particle size: 20 nm) were used as raw material fine particles, the tetragonal ratio of the crystal structure after sintering at 1000° C. was 95%, showing the same result as that of Example 4.

[0115] As shown in Example 11, even if the amount of yttrium nitrate added is reduced, the zirconium oxide fine particles can be coated.

[0116] As shown in Examples 12 and 13, even when the amount of yttrium nitrate added is increased, the zirconium oxide fine particles can be coated. In Examples 12 and 13, it is presumed that yttrium oxide without solid solution is also generated based on the observation of the XRD pattern of yttrium oxide.

[0117] <Examples 14 to 21, Comparative Example 3>

[0118] The effect of the size of zirconium oxide fine particles (hereinafter referred to as raw material fine particles) used in the coating step will be described. Since raw material fine particles with a wide particle size distribution are also used, the particle size is evaluated here by specific surface area.

[0119] According to Example 2, coated zirconium oxide particles were obtained using raw material particles having specific surface areas shown in Table 2. 2 / g) and calcined to adjust the specific surface area. The coating compound was uniformly set to 12 mol% in terms of yttrium hydroxide. The obtained coated zirconium oxide particles were calcined at 1000°C in the same manner as in Examples 1 to 13, and the crystal structure was evaluated by XRD measurement. The tetragonal ratio after calcination and the specific surface area of ​​the raw material particles are shown in Table 2.

[0120]

Table 2

[0121]

[0122] As shown in Table 2, it can be seen that as the specific surface area of ​​the raw material particles increases, the tetragonal ratio increases. Under the sintering conditions, especially Examples 14 to 17, i.e., the specific surface areas of 75 to 140 m 2 / g range, the tetragonal ratio is about 90%, and Y is a tetragonal stabilizing element, which is found to work more effectively. This is believed to be because the smaller the particle size, the more uniform the solid solution of Y is at the molecular level.

[0123] <Reference Examples 1 to 4>

[0124] The degree of densification of the sintered bodies produced using the coated zirconia fine particles was evaluated.

[0125] 〔Sintered body production〕

[0126] 4 g of coated zirconium oxide fine powder was used to produce a compact by a uniaxial press at a pressure of 0.5 t. As an evaluation of densification, the compact before and after sintering was measured with a vernier caliper and the density of the compact was divided by the theoretical density of zirconium oxide (6.0 g / cm 3 ) and calculate the relative density (%). The sintering temperature was set at 200°C for 1 hour, 1000°C for 3 hours, and 1200°C for 3 hours, and the heating rate was set at 4°C / min from 20°C to 1000°C and 2°C / min from 1000°C to 1200°C. Table 3 shows the relative density of the sintered body.

[0127] In Reference Example 1, zirconium oxide particles without a coating stabilizer were used (Comparative Example 1), in Reference Example 2, the coated zirconium oxide particles of Example 1 were used, in Reference Example 3, the coated zirconium oxide particles of Example 4 were used, and in Reference Example 4, commercially available partially stabilized zirconium oxide was used.

[0128]

Table 3

[0129]

[0130] ※1 Relative density (%) = (W / V) / d0×100

[0131] W: Mass of coated zirconium oxide particles (g)

[0132] V: Volume of the formed body (cm 3 )

[0133] d0: theoretical density of zirconium oxide (=6.0 g / cm 3 )

[0134] ※2 The content of the commercial product of Reference Example 4 is (1) calculated by Y2O3 conversion, and (2) calculated by Al2O3 conversion.

[0135] As shown in Reference Example 1, the zirconium oxide fine particles not coated with a stabilizer could not produce a molded body per se. On the other hand, when the zirconium oxide fine particles coated with only yttria in Reference Example 2 were used, a sintered body could be produced without cracks or damage.

[0136] As shown in Reference Example 3, a sintered body was produced using zirconium oxide fine particles whose surfaces were coated not only with yttrium hydroxide but also with aluminum hydroxide. As a result, the sintered body could be made denser than the commercial product shown in Reference Example 4.

[0137] Embodiment 22

[0138] 100 g of the powder of the coated zirconium oxide particles obtained in Example 4 was mixed with 500 g of pure water, and acetic acid was added dropwise to form a pH of 4 to prepare a mixed solution. The obtained mixed solution was stirred for 30 minutes with a dispersing stirrer for coarse dispersion. The obtained mixed solution was dispersed in a medium-type wet disperser. The dispersion of Example 22 was obtained by dispersing while confirming the particle size during the process. The dispersed particle size of the coated zirconium oxide particles in the obtained dispersion was determined by the following method. In addition, as Reference Example 5, instead of the coated zirconium oxide particles of Example 4, zirconium oxide particles of raw materials that were not coated were used, and a dispersion was prepared in the same manner, and the dispersion was also evaluated in the same manner. The results are shown in Table 4.

[0139] Embodiment 23

[0140] 120 g of the powder of the coated zirconium oxide particles obtained in Example 4, 30.0 g of 3-methacryloyloxypropyltrimethoxysilane (trade name: KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.), and 250 g of methyl ethyl ketone (MEK) were mixed and stirred for 30 minutes using a dispersing mixer for coarse dispersion. The resulting mixed solution was dispersed using a medium-type wet disperser. The dispersion of Example 23 was obtained by dispersing while confirming the particle size during the process. The dispersed particle size of the coated zirconium oxide particles in the obtained dispersion was determined by the following method. In addition, as Reference Example 6, instead of the coated zirconium oxide particles of Example 4, zirconium oxide particles of the raw material that were not coated were used, and a dispersion was prepared in the same manner, and the dispersion was also evaluated in the same manner. The results are shown in Table 4.

[0141] <Method for measuring the dispersed particle size of coated zirconium oxide fine particles in a dispersion>

[0142] The dispersed particle size of the coated or uncoated zirconium oxide fine particles in the dispersion liquid one day after preparation (stored at 25° C.) was measured at 25° C. using a dynamic light scattering particle size distribution measuring apparatus LB-500 manufactured by Horiba, Ltd. The results are shown in Table 4. It can be seen that even when the coated zirconium oxide fine particles of the present invention are used, a dispersion liquid having a good dispersion state can be prepared in the same manner as uncoated zirconium oxide fine particles.

[0143]

Table 4

[0144] .

Claims

1. A coated zirconium oxide fine particle comprising zirconium oxide fine particles and a coating layer coating the surface of the fine particles, wherein: The coating layer comprises a hydroxide of one or more metal elements selected from Mg, Ca, Al and rare earth elements, wherein the metal elements contain at least Y, the amount of the coating compound in the coating layer is 12 to 45 mol% relative to the zirconium oxide of the zirconium oxide fine particles, and the average particle size is 3 to 50 nm. Specific surface area is 20~500m 2 / g.

2. A method for producing coated zirconium oxide particles, wherein: In an aqueous dispersion containing zirconium oxide fine particles, ions of one or more metal elements selected from Mg, Ca, Al and rare earth elements and an additive that reacts with the ions to form a water-insoluble compound are reacted to precipitate a hydroxide containing the metal element on the surface of the zirconium oxide fine particles to obtain coated zirconium oxide fine particles, wherein the metal element contains at least Y, The amount of the coating compound is 12 to 45 mol% based on the zirconium oxide in the zirconium oxide fine particles. The average particle size of the coated zirconium oxide particles is 3 to 50 nm. The specific surface area of ​​the coated zirconium oxide particles is 20 to 500 m 2 / g.

3. The method for producing coated zirconium oxide particles according to claim 2, wherein: The aforementioned additive is an alkaline substance.

4. The method for producing coated zirconium oxide particles according to claim 2 or 3, wherein: After the coated zirconium oxide fine particles are obtained, the aforementioned additives are removed from the coated zirconium oxide fine particles.

5. The method for producing coated zirconium oxide particles according to claim 2 or 3, wherein: After obtaining the coated zirconium oxide fine particles, the coated zirconium oxide fine particles are washed with water. 6 . The method for producing coated zirconium oxide fine particles according to claim 2 , wherein the obtained coated zirconium oxide particles are dried at 200° C. or lower.

7. The method for producing coated zirconium oxide particles according to claim 2 or 3, wherein: The average particle size of the zirconium oxide fine particles is 3 to 50 nm.

8. The method for producing coated zirconium oxide particles according to claim 2 or 3, wherein: The aqueous dispersion, the aqueous solution containing the compound of the metal element, and the additive are mixed. 9 . A method for producing a zirconia sintered body, comprising: a step of producing coated zirconia fine particles by the method according to claim 2 ; and a step of sintering the produced coated zirconia fine particles. 10 . A method for producing a coated zirconium oxide fine particle dispersion, comprising the step of dispersing the coated zirconium oxide fine particles according to claim 1 in a dispersion medium. 11 . A method for producing a nanocomposite, comprising the step of dispersing the coated zirconium oxide fine particles according to claim 1 in a dispersion medium.

Citation Information

Patent Citations

  • Production of zirconia sol

    JP1993170442A

  • Zirconia fine powder, its manufacturing method and its use

    JP2008024555A

  • Zirconia composite microparticle, zirconia composite microparticle dispersion liquid, and method for producing zirconia composite microparticle

    JP2009227507A

  • Partially stabilized zirconia ceramic and producing method of the same

    JP2010137998A

  • Zirconia sintered body and manufacturing method therefor

    JP2015221727A